Sub-okra leaf shape conferred via chromosomal introgression from Gossypium barbadense L. improves photosynthetic productivity in short-season cotton (Gossypium hirsutum L.) - Jiang, Hui; Ma, Xiongfeng; Shi, Jialiang; Gao, Mingwei; Zhang, Xianliang; Zhang, Chao; Chai, Qichao; Wang, Yongcui; Wang, Xiuli; Wang, Jiabao; Chen, Ying; Zhang, Donglou; et al. (Frontiers in Plant Science, 2024)
Leaf shape is a vital agronomic trait that affects plant and canopy architecture, yield, and other production attributes of upland cotton. Compared with normal leaves, lobed leaves have potential advantages in improving canopy structure and increasing cotton yield. A chromosomal introgression segment from Gossypium. barbadense L. conferring sub-okra leaf shape to Gossypium. hirsutum L. was identified on chromosome D01.To determine the effects of this transferred sub-okra leaf shape on the leaf anatomical characteristics, photosynthesis-related traits , and yield of short-season cotton, we performed a field experiment with three sets of near-isogenic lines carrying okra, sub-okra, and normal leaf shape in Lu54 (L54) and Shizao 2 (SZ2) backgrounds. Compared with normal leaves, sub-okra leaves exhibited reduced leaf thickness and smaller leaf mass per area; moreover, the deeper lobes of the sub-okra leaves improved the plant canopy structure by decreasing its leaf area index by 11.24% to 22.84%. Similarly, the intercepted PAR rate of lines with sub-okra leaf shape was also reduced. The chlorophyll content of sub-okra leaves was lower than that of okra and normal leaf shapes; however, the net photosynthetic rate of sub-okra leaves was 8.17%-29.81% higher than that of other leaf shapes at most growth stages. Although the biomass of lines with sub-okra leaf shape was less than that of lines with normal leaves, the average first harvest yield and total yield of lines with the sub-okra leaf shape increased by 6.36% and 5.72%, respectively, compared with those with normal leaves. Thus, improvements in the canopy structure and photosynthetic and physiological characteristics contributed to optimizing the light environment, thereby increasing the yield of lines with sub-okra leaf shape. Our results suggest that the sub-okra leaf trait from Gossypium. barbadense L. may have practical applications for cultivating short-season varieties with high photosynthetic efficiency, and improving yield, which will be advantageous for short-season varieties.